Transgression as a Result of Cultural Contact - Tadeusz Paleczny (Ksiegarnia Akademicka Publishing, 2021)
This article focuses on the processes of transferring the cultural elements between different racial, ethnic and religious groups. The transmission of various cultural products containing symbols, norms and values is the result of crosscultural contact and multicultural relations. Transgression is a kind of exchange and transcultural diffusion between two or more different cultural groups. The processes of common cross-cultural, two-directional influences lead to the creation of new types of universalized identity and create the transcultural forms of social as well as political organization.